The nesting and some other habits of Alopochen, Nettapus, Plectropterus and Sarkidiornis - Pitman, Captain C R S (Wildfowl, 1965)
African 'geese' are catholic in their choice of nest-sites. Most Egyptian and Spur-winged Geese nest on dry ground, but may use holes in trees, or old arboreal nests of other birds. Pygmy Geese occasionally nest on the ground but more often in trees or on buildings. The Knob-bill nests in trees and in Africa at least also on the ground. Clutch-sizes and parental behaviour are discussed. There is some evidence that Sarkidiornis may often be polygamous in Africa, though apparently not in India. Alopochen and Plectropterus roost on water, the latter also sometimes on dry land. Sarkidiornis roosts chiefly in trees, though sometimes on mudbanks or floating islets. The roosting places of Nettapus are not known. Flocks of Alopochen and Plectropterus sometimes cause serious damage to crops, by trampling or nibbling maize, beans, and sweet potatoes and pulling up entire ground-nut plants.